2018
DOI: 10.18196/jmmr.7268
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Clinical Pathway Implementation on Cerebral Infarction in the Inpatient Care Unit of Bantul X Hospital

Abstract: Stroke remains one of the major health problems, not only in Indonesia but also in the world. The improvement of stroke service process is expected to support better outcomes of stroke service quality. One of the clinical management uses is the implementation of clinical pathway (CP). The purpose of this study was to explore the implementation of clinical pathway cerebral infarction in the inpatient unit of Bantul X hospital. A convergent parallel mix-method design with case study approach. The quantitative sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Periodic evaluation of the content provides the latest references for updates. 12 This study found that CP was implemented in 2019, but in practice, it did not work out.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Periodic evaluation of the content provides the latest references for updates. 12 This study found that CP was implemented in 2019, but in practice, it did not work out.…”
Section: Discussionmentioning
confidence: 82%
“…Safitri found that the hospital organized a CP drafting team that met periodically with outpatient and inpatient paramedics. 12 The major goal of the organization is to build solid commitments among healthcare professionals, including medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations in this study were that the provision of intervention to health workers was not directly to every healthcare practitioner but by seminars or CP material debriefs due to workplace protocols to mitigate and control the transmission of COVID-19. The limited social engagement aspect of this study's CP implementation towards healthcare practitioner may result in low adherence towards CP compliance, where adherence and compliance have been reported to be strongly associated [65,66]. Knowledge from CP intervention is often not always followed by behavioral changes, especially when pressure from external factors (egalitarianism, facilities, or systems) such as forcing the subject to change behavior [67,68].…”
Section: Limitations and Future Researchmentioning
confidence: 89%
“…The most crucial goal in health care is beneficial outcomes for patients and communities. The desired outcomes depend on the quality of health or hospital services (Fitri and Sundari, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, clinical process (clinical care) is regulated in medical service guidelines and the standards of nursing care or generally referred to as clinical guidelines. One of the clinical guidelines is the clinical pathway that has the potential to be used as a tool to guarantee and improve the quality of the clinical care process (Fitri and Sundari, 2018).…”
Section: Introductionmentioning
confidence: 99%